Asymptotic Behavior of Positive Solutions of a Competitive System Subject to Environmental Noise. (2nd March 2015) - Xiang, Huili; Fang, Zhuang; Li, Zuxiong; Liu, Zhijun
Abstract : A competitive system subject to environmental noise is established. By using the theory of stochastic differential equations and Lyapunov function, sufficient conditions for the existence, uniqueness, stochastic boundedness, and global attraction of the positive solution of the above system are established, respectively. An example together with its corresponding numerical simulations is presented to confirm our analytical results.